2016
DOI: 10.3389/fpls.2016.00470
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Peroxide, Signaling in Disguise during Metal Phytotoxicity

Abstract: Plants exposed to excess metals are challenged by an increased generation of reactive oxygen species (ROS) such as superoxide (O2•-), hydrogen peroxide (H2O2) and the hydroxyl radical (•OH). The mechanisms underlying this oxidative challenge are often dependent on metal-specific properties and might play a role in stress perception, signaling and acclimation. Although ROS were initially considered as toxic compounds causing damage to various cellular structures, their role as signaling molecules became a topic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
96
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 147 publications
(113 citation statements)
references
References 274 publications
(386 reference statements)
0
96
0
4
Order By: Relevance
“…The volatility of such materials as butanediol, or effector movement through the plant, as demonstrated for AHSLs , could be involved in the systemic nature of the responses. Reactive oxygen species (ROS) output in plant cells contacted with the elicitors is speculated to be a primary signal (Cuypers et al, 2016;Hossain et al, 2015). For instance, phenazines stimulate ROS production in contacted cells through their electron shuttle potential (Briard et al, 2015).…”
Section: Probiotic Trait: Altered Host Immunity Is the Phenomenon Of mentioning
confidence: 99%
“…The volatility of such materials as butanediol, or effector movement through the plant, as demonstrated for AHSLs , could be involved in the systemic nature of the responses. Reactive oxygen species (ROS) output in plant cells contacted with the elicitors is speculated to be a primary signal (Cuypers et al, 2016;Hossain et al, 2015). For instance, phenazines stimulate ROS production in contacted cells through their electron shuttle potential (Briard et al, 2015).…”
Section: Probiotic Trait: Altered Host Immunity Is the Phenomenon Of mentioning
confidence: 99%
“…Pb pollution may be naturally occurring or result from anthropogenic activities (Yadav, 2010), creating potential hazards to ecosystems (Lantzy and Mackenzie, 1979). Pb pollution has also been a serious threat to human health and food safety (Cuypers et al, 2016), especially harmful to young children (Datko-Williams et al, 2014). Over the last decade, evidence has been shown that Pb exposure-related health injury occur already at lower blood Pb levels than previously documented (Henry et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Decreases in Cd uptake can also be provided by soil microorganisms, which increases solubilization of nutrients that may compete with Cd in sites for its absorption and translocation (Dourado et al, 2013;Madhaiyan et al, 2007;Sebastian & Prasad, 2016a). In addition, some organisms from soil microbiological community can change plant response to Cd exposure by altering hormonal balance of plants, and by modifying generation of reactive oxygen species, which are important signaling molecules (Cuypers et al, 2016;Dourado et al, 2013;Madhaiyan et al, 2007).…”
Section: Cadmium-induced Modifications In the Nutrient Uptake And Dmentioning
confidence: 99%
“…Once within the plant, Cd triggers oxidative stress, disturbs nutrient uptake and distribution, impairs photosynthesis, triggers chromosomal aberrations, and decreases yield (Bayçu, Gevrek‐Kürüm, et al., ; Bayçu, Rognes, et al., ; Carvalho et al., ; Gallego et al., ; Gratão, Polle, Lea, & Azevedo, ; Gratão et al., ; Hédiji et al., ; Sebastian & Prasad, ,). Multiple studies have shown great damages in cell systems due to the overproduction of reactive oxygen and nitrogen species (the so‐called ROS and RNS, respectively) as a consequence of plant exposure to heavy metals (Alves et al., ; Branco‐Neves et al., ; Cuypers et al., ; Fidalgo, Freitas, Ferreira, Pessoa, & Teixeira, ; Fidalgo et al., ; Gallego et al., ; Iannone, Groppa, & Benavides, ). To a certain extent, plants can cope with the heavy metal‐induced oxidative stress by employing enzymatic and nonenzymatic antioxidant machineries, which encompass the modulation of superoxide dismutase (SOD, EC 1.15.1.1), catalase (CAT, EC 1.11.1.6), ascorbate peroxidase (APX, EC 1.11.1.11) activities, among other enzymes, as well as the synthesis of amino acids, soluble sugars, glutathione, and their derivates (Cuypers et al., ; Gallego et al., ; Jozefczak, Remans, Vangronsveld, & Cuypers, ; Méndez, Pena, Benavides, & Gallego, ; Štolfa, Pfeiffer, Špoljarić, Teklić, & Lončarić, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation